Isolation and Identification of Biosurfactant-Producing Bacteria in An-aerobic Palm Oil Waste Pools at PT. Aek Loba Plantation - Sipahutar, Lara Santi Hemat; Rasyidah; Mayasari , Ulfayani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Biosurfactant-producing bacteria are bacteria that have alternative energy sources, namely surfactants which contain hydrophilic and hydrophobic groups based on their molecular structure so that they can survive between different polar and hydrogen bonding fluids. Palm oil mill liquid waste is waste in the form of water or liquid, oil and organic solids produced from the processing of palm oil. The purpose of this study was to determine the genera of biosurfactant-producing bacteria found in palm oil wastewater in the an-aerobic pond of PT. Aek Loba plantation and to find out the bacterial species with the highest emulsification index. This study used descriptive methods and identification of bacteria through morphological characterization, gram staining tests and biochemical tests. Bacteria were isolated from palm oil wastewater by dilution method 10-4, 10-5 and 10-6. Bacterial emulsification index is calculated by emulsification test. In this study, 8 biosurfactant-producing bacterial isolates were found, consisting of 2 Proteus genus isolates, 2 Enterobacter genus isolates, 2 Bacillus genus bacterial isolates and 2 Pluralibacter genus isolates. The bacteria that had the highest emulsification index was Pluralibacter gergoviae with an emulsion index of 43% which was identified by molecular testing.